Algorithmic method for assessing urinary incontinence in elderly women. - Hilton, P (1981)
In young patients the assessment of urinary incontinence is based increasingly on the results of complex urodynamic investigations. The value of such techniques in the elderly, however, is as yet unproved. Based on the clinical and urodynamic findings in 100 incontinent elderly women an algorithmic method for managing such patients was devised. A retrospective study comparing the algorithmic outcome with the results of standard urodynamic assessment showed that 60% of invasive investigations could be avoided by this method with minimal loss of diagnostic accuracy.